2011
DOI: 10.1097/ccm.0b013e31821201a5
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin for reduced antibiotic exposure in the critical care setting: A systematic review and an economic evaluation*

Abstract: Procalcitonin-guided antibiotic therapy is associated with a reduction in antibiotic usage that, under certain assumptions, may reduce overall costs of care. However, the overall estimate cannot rule out a 7% increase in hospital mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
105
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(112 citation statements)
references
References 35 publications
3
105
0
4
Order By: Relevance
“…The use of procalcitonin [64,144,145] or similar biomarkers may facilitate discontinuance of antibiotics in a patient with clinical improvement, although one recent study failed to show any benefit of daily procalcitonin measurement [146]. Table 4) should be rapidly referred to an intensive care unit (ICU) In 2004, the "Surviving Sepsis Campaign" guidelines recommended the use of EGDT [147] based on one large randomized trial [93].…”
Section: The Empirical Treatment Must Be Optimized When Microbiology mentioning
confidence: 99%
“…The use of procalcitonin [64,144,145] or similar biomarkers may facilitate discontinuance of antibiotics in a patient with clinical improvement, although one recent study failed to show any benefit of daily procalcitonin measurement [146]. Table 4) should be rapidly referred to an intensive care unit (ICU) In 2004, the "Surviving Sepsis Campaign" guidelines recommended the use of EGDT [147] based on one large randomized trial [93].…”
Section: The Empirical Treatment Must Be Optimized When Microbiology mentioning
confidence: 99%
“…There is strong evidence that PCT-guided care management results in reductions in antibiotic exposure and possibly costs [33,35,37,38,[48][49][50][51][52][53]. For example, a comparative effectiveness summary report from the US Agency for Healthcare Research and Quality ("AHRQ"; 2012) concluded that there was high strength of evidence in support of PCT reducing antibiotic usage, with relative reductions ranging from 21% to 38% [53].…”
Section: Introductionmentioning
confidence: 99%
“…Based on published randomized trials of PCT-guided treatment in Canadian hospital intensive care units, Heyland et al conducted a cost-minimization analysis based on the costs of PCT testing and antibiotic acquisition and administration [51]. PCT-guided strategies were associated with a significant reduction in antibiotic use, and PCT-guided care was not associated with any differences in hospital mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the evidence that PCT-guided care management results in reduction of antibiotic exposure and hospital length of stay while improving the timing of diagnosis and treatment, the existing economic literature on PCT is limited and presents several limitations [9,10]. The paper by Phillip Schuetz and Colleagues, which is published in this issue of Clinical Chemistry and Laboratory Medicine, therefore, is very welcome as it adds further evidence of the substantial cost savings associated with PCT protocols of ARI in comparison to usual care [11].…”
mentioning
confidence: 99%